Existence And Values Of Islamic Education: (Reflection of Ma'balla Local Wisdom of Kaluppini Community, Enrekang Regency) - Rahman, Abd.; Herman, Arfian Alinda; Suhartina, Suhartina; Hamdanah, Hamdanah; Bahtiar, Bahtiar (Jurnal Kawakib, 2024)
The ma'balla tradition in Kaluppini Village, Enrekang Regency, is a unique communal eating ritual that embodies Islamic educational values. This study, employing a descriptive qualitative method through interviews, observations, and documentation with local leaders and the community, explores the faith, moral, psychological, and social aspects. Ma'balla highlights faith through collective prayers, instills morality by ensuring equality in food distribution, and fosters social education through the spirit of cooperation involving the entire community. A notable feature is the active involvement of men in food preparation, reflecting a rare practice of gender equality in such traditions. Beyond preserving cultural heritage, ma'balla serves as a medium for teaching Islamic values, strengthening social bonds, and maintaining the cultural identity of the Kaluppini community. This tradition demonstrates how local wisdom can integrate spiritual and communal values, offering a meaningful model for Islamic education rooted in cultural practices.